2012
DOI: 10.2151/jmsj.2012-505
|View full text |Cite
|
Sign up to set email alerts
|

Observed Trends in Surface Air Temperatures and Their Extremes in Thailand from 1970 to 2009

Abstract: Based on updated quality controlled daily records, extreme events were defined using temperature indices proposed by the Commission for Climatology/Climate Variability and Predictability project's Expert Team on Climate Change Detection, Monitoring and Indices, and temporal trends during the 1970-2009 period were examined in Thailand. Results revealed that Thailand has indeed experienced significant country-wide warming over the last four decades, and extreme events associated with both the cold and warm extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 49 publications
8
27
0
Order By: Relevance
“…It was observed that the annual number of hot days and warm nights had increased significantly whereas the annual number of cool days and cold nights had decreased significantly, consistently over the whole Asia Pacific Region. Moreover, at the national level, for example in Thailand (Limjirakan and Limsakul, ) and in the Philippines (Cinco et al , ), similar results of spatially coherent warming signals were documented. Siswanto et al () analysed 134 years of daily temperature data collected at the Jakarta Observatory station and reported that the maximum temperature had increased at a rate of 2.12 °C per century, which was larger than that of the minimum temperature.…”
Section: Introductionmentioning
confidence: 65%
“…It was observed that the annual number of hot days and warm nights had increased significantly whereas the annual number of cool days and cold nights had decreased significantly, consistently over the whole Asia Pacific Region. Moreover, at the national level, for example in Thailand (Limjirakan and Limsakul, ) and in the Philippines (Cinco et al , ), similar results of spatially coherent warming signals were documented. Siswanto et al () analysed 134 years of daily temperature data collected at the Jakarta Observatory station and reported that the maximum temperature had increased at a rate of 2.12 °C per century, which was larger than that of the minimum temperature.…”
Section: Introductionmentioning
confidence: 65%
“…[8] reported a significant decreasing trend in the USA, Europe, Middle Asian and Siberian regions of the former Soviet Union for the period of . Decreasing trends were also reported in India [1,17,52], Canada [2], Italy [10], Japan [12], China [13][14], Australia [11], and Thailand [15][16]. [53] pointed out that evaporation for New Zealand was decreasing 2 mm annually since 1970.…”
Section: Figure 3 Trend Analysis Results For Mean Seasonal Evaporationmentioning
confidence: 94%
“…Increasing trends in evaporation were reported in Israel [3], Brazil [4], eastern Asia including Tibetan Plateau, China and Japan [5], western Africa [6] and Iran [7]. On the other hand, decreasing trends were also reported in the USA [8], the USA and former Soviet Union [9], Italy [10], Australia [11], Japan [12], China [13][14], Thailand [15][16], Canada [2], and India [1,17]. In Turkey, although many researchers [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] have investigated climatic changes in temperature and precipitation, the same interest has not been shown for evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Daily mean maximum air temperatures in these months reach 38-40 • C, providing severe heat stress under continuing drought conditions [12]. There is additional concern for the future of this and other forest communities in Southeast Asia because of potential impacts of increases in mean and extreme temperatures that are predicted to occur in the future under models of global change [16,17].…”
Section: Introductionmentioning
confidence: 99%